The Disease Phenotype of Adenomyosis-Affected Women Correlates With Specific Serum Cytokine Profiles. (February 2019) - Bourdon, Mathilde; Santulli, Pietro; Chouzenoux, Sandrine; Maignien, Chloé; Bailly, Karine; Andrieu, Muriel; Millischer, Anne-Elodie; Doridot, Ludivine; Marcellin, Louis; Batteux, Fréderic; Chapron, Charles
Background: Adenomyosis (ADE) is an enigmatic uterine disorder. Several types have been previously described: diffuse adenomyosis (DIF-ADE), focal adenomyosis (FOC-ADE), and association of focal and diffuse lesions (FOC/DIF-ADE). Abnormal immune phenomena have been described that may provide an understanding of the pathophysiology of adenomyosis. However, the immune imbalance in adenomyosis is however still poorly understood. Objective: To compare serum cytokine profiles for the various adenomyosis phenotypes in adenomyosis versus disease-free women. Materials and Methods: This cohort study included 80 women. Based on the magnetic resonance imaging (MRI) findings, the women were allocated to the ADE group (n = 60) and the control group (n = 20). The ADE group was further subdivided according to the phenotype: DIF-ADE, FOC-ADE, and FOC/DIF-ADE. For all of the women, serum cytokine levels were assayed by multiplex immunoassay. Results: Serum levels of interleukin (IL) 23 (237.77 pg/mL ± 70.97 in the ADE-group versus 1855.04 ± 1411.33 in the control group, P = .019), IL25 (31.98 ± 8.54 vs 222.08 ± 170.90, respectively, P = .006), IL31 (10.13 ± 3.83 vs 91.51 ± 71.21, respectively, P = .034), IL33 (3.77 ± 1.23 vs 17.86 ± 11.49, respectively, P = .016), and IL17F (16.29 ± 2.35 vs 30.12 ± 8.29, respectively, P = .042) were significantly lower in the women with adenomyosis when compared to the controls In the FOC/DIF-ADE group, the serum levels of IL23, IL31, IL25, and IL33 were significantly lower when compared to the control group. Conclusion: Serum levels of IL23, IL31, IL25, and IL33 were lower in women exhibiting adenomyosis forms with associated diffuse and focal lesions when compared with controls. The pathogenesis of adenomyosis may be associated with an immunotolerant process that is more pronounced in associated FOC/DIF-ADE.